Seasonal physiological responses in the greater thick-tailed galago (Otolemur crassicaudatus) - Tordiffe, Adrian Stephen Wolferstan (University of Pretoria, 2024)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2023.